Comparison of Feasibility and Profitability of Sugarcane Farming Between Cane Plant (PC) and Ratoon Cane (RC) in Lemahabang District, Cirebon Regency - Akhri, Rabiul; Zaelani, Muhammad Akbar; Azi, Maullana; Faqih, Achmad; Aisyah, Siti (International Journal Labs, 2025)
This study was conducted from May to June 2025 and aims to compare the feasibility and profitability of sugarcane farming between the Plant Cane (PC) and Ratoon Cane (RC) cultivation systems in Lemahabang District. The methods used include cost, revenue, and revenue analysis, as well as a number of economic indicators, namely Net Farm Income (NFI), Revenue-Cost Ratio (R/C), Benefit-Cost Ratio (B/C), Return on Investment (ROI), Break Even Point (BEP), and Net Profit Margin (NPM). The results of the analysis showed that RC farming has a lower average production cost and higher income than PC. The R/C (3.22), B/C (2.22), and high ROI on RC indicate that this system is economically more efficient and nominally profitable. However, the NPM for RC was negative (-18.74%), indicating the risk of losses to some farmers due to yield fluctuations or cost inefficiencies, while PC showed a positive NPM of 19.03%, reflecting the stability of profit margins. The results of the Mann–Whitney test showed that all indicators of feasibility and profitability differed significantly between the two systems (p < 0.05). Thus, RC systems are nominally superior but have higher risk, while PC systems are more stable in terms of profitability albeit with lower net profits. The selection of cultivation systems should be adjusted to the business objectives, managerial capacity, and risk tolerance of each farmer.